A Simplified and Cost-Effective Treatment Approach for Combination Syndrome: A Case Report - M. Krishna1 , Abhijita Mohapatra2 , Gopal Krishna Choudhury3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Combination syndrome is a dental condition, mostly observed in patients with a completely maxillaryedentulous arch and a partially edentulous mandibular arch persisting only the anterior teeth. Specific oraldestructive changes are often seen in patients. The manifestation of this syndrome consists of resorptionin the anterior maxillary ridge, overgrowth of tuberosities, and supra eruption of mandibular anterior andreduced alveolar ridge height in combination with hypertrophic and atrophic changes in the maxilla andmandible. Complications involved in chewing and mastication are of special apprehension in such a patient.Predictable prognosis can be offered by overdentures. This article attempts to provide a simplified and costeffective approach to this type of treatment modality by a case report.